PFDN2 promotes cell cycle progression via the hnRNPD-MYBL2 axis in gastric cancer - He, Qiuming; Ding, Zheyu; Chen, Tingna; Wu, Haitao; Song, Jialing; Xiang, Zhenxian; Yang, Chaogang; Wang, Shuyi; Xiong, Bin (Frontiers in Oncology, 2023)
Gastric cancer (GC) is a major health burden worldwide, but our understanding of GC is limited, and the prognosis is poor. Novel therapeutic strategies and biomarkers are urgently needed to improve GC patient outcomes. Previously, we identified PFDN2 as a novel key gene in gastric cancer based on its differential expression between cancer and normal tissues. However, the role and underlying mechanisms of PFDN2 in GC remain elusive. In this article, we demonstrated that PFDN2 is highly expressed in GC and that upregulation of PFDN2 is associated with the progression of GC. We further found that PFDN2 could promote cell cycle progression by promoting MYBL2 expression. Mechanistically, we demonstrated that PFDN2 could upregulate MYBL2 expression by facilitating the nuclear translocation of hnRNPD, and thus promoting MYBL2 transcriptional program. In conclusion, we found that PFDN2 promotes cell cycle progression via the hnRNPD-MYBL2 axis and may serve as a potential biomarker and therapeutic target for GC.